The impact on adolescents of a Transtheoretical Model-based programme on fruit and vegetable consumption - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2019)
Objective: The present study aimed to evaluate the impact of a Transtheoretical Model-based programme titled 'Fruit & Vegetable-Friendly' on the fruit and vegetable (F&V) consumption of adolescents. Design: A quasi-experimental study. The 'Fruit & Vegetable-Friendly', a multicomponent intervention based on the Transtheoretical Model, was completed in eight weeks. The data were collected one week before the intervention, one week after the completion of the intervention and six months after the post-test with an F&V intake questionnaire and the stages of change, processes of change (alpha = 0 center dot 91), situational self-efficacy (alpha = 0 center dot 91) and decisional balance (alpha = 0 center dot 90 for pros, alpha = 0 center dot 87 for cons) scales. Data were analysed with the Friedman, Wilcoxon and marginal homogeneity tests. Setting: A public secondary school in Istanbul, Turkey. Participants: Seven hundred and two adolescents. Results: The mean (sd) F&V intake of adolescents in the passive stages rose from the daily average at the time of the pre-test of 3 center dot 40 (1 center dot 79) portions to 5 center dot 45 (2 center dot 54) portions on the post-test and to 5 center dot 75 (2 center dot 70) portions on the follow-up test (P < 0 center dot 01). While the students in the passive stages represented 41 center dot 6 % of the participants prior to the programme, this rate fell to 23 center dot 7 % at the post-test and to 22 center dot 7 % at the follow-up. Students in the active stages first represented 58 center dot 5 % of the participants; this rate rose to 76 center dot 4 % at the post-test and to 77 center dot 2 % at the follow-up test. Conclusions: The programme was effective in increasing the amount of F&V the adolescents consumed on a daily basis.
Keywords: Fruits and vegetables; Adolescent; Transtheoretical Model; Behaviour change; SELF-EFFICACY; INTERVENTION; TRANSITIONS; VARIABLES; PATTERNS; STAGE